Effects of supplementation of chromium histidinate on glucose, lipid metabolism and oxidative stress in cats - Machac, Nina; Karasu, Gulsah Kaya; Şahin, Nurhan; Orhan, Cemal; Şahin, Kazım; Iben, Christine (Wiley, 2019)
In recent years, two meta-analyses of chromium (Cr) supplementation have shown beneficial effects on glucose metabolism. Chromium histidinate (CrHis) reduces serum glucose levels in rats fed a high-fat diet but no study has been conducted on cats until now. The aim of this study was to examine the effects of CrHis on glucose and lipid metabolism in cats. To challenge the glucose metabolism, 16 cats were fed a high-carbohydrate high-fat diet for three months. One group (n = 8) received 800 ug CrHis per day for two months, while the other group (n = 8) served as control group. An oral glucose tolerance test was conducted, blood samples were taken, and biochemical parameters and oxidative stress were measured. CrHis serum levels were significantly increased (p = 0.027) in the treatment group, while fructosamine levels were significantly lower (p = 0.029) in the control group. In both groups, glucose (p < 0.01), b-hydroxy-butyrate (p = 0.024) and 8-hydroxy-deoxyguanosine (p = 0.028) levels decreased significantly and cholesterol levels increased significantly (p < 0.01). In conclusion, CrHis did not improve glucose or lipid metabolism and did not affect oxidative stress in healthy cats.
Keywords: cats; chromium histidinate; glucose metabolism; glucose tolerance; lipid metabolism; oxidative stress